Effects of large herbivores on tundra vegetation in a changing climate, and implications for rewilding. (22nd October 2018) - Olofsson, Johan; Post, Eric
Abstract : In contrast to that of the Pleistocene epoch, between approximately 2.6 million and 10 000 years before present, the extant community of large herbivores in Arctic tundra is species-poor predominantly due to human extinctions. We here discuss how this species-poor herbivore guild influences tundra ecosystems, especially in relation to the rapidly changing climate. We show that present herbivore assemblages have large effects on tundra ecosystem composition and function and suggest that the effect on thermophilic species expected to invade the tundra in a warmer climate is especially strong, and that herbivores slow ecosystem responses to climate change. We focus on the ability of herbivores to drive transitions between different vegetation states. One such transition is between tundra and forest. A second vegetation transition discussed is between grasslands and moss- and shrub-dominated tundra. Contemporary studies show that herbivores can drive such state shifts and that a more diverse herbivore assemblage would have even higher potential to do so. We conclude that even though many large herbivores, and especially the megaherbivores, are extinct, there is a potential to reintroduce large herbivores in many arctic locations, and that doing so would potentially reduce some of the unwanted effects of a warmer climate. This article is part of the theme issue 'Trophic rewilding: consequences for ecosystems under global change'.